Fullerene (C60) Nanowires: The Preparation, Characterization, and Potential Applications. Issue 4 (25th May 2020) - Fan, Xiao; Soin, Navneet; Li, Haitao; Li, Hua; Xia, Xiaohong; Geng, Junfeng
Abstract : Fullerene (C60 ) nanowires have attracted significant attention in the past two decades due to their outstanding chemical and physical properties, which render the material a wide range of potential applications. Much effort has been devoted to exploring the growth methods, structural and compositional characterizations, and application‐related investigations of this novel carbon nanomaterial. Here, we present a review of C60 nanowires in which we will first describe the recent development in the material preparations, analytical techniques, crystal structures, chemical compositions, and the investigations of polymerization processes. Afterward, we will discuss the mechanistic studies on the nanowires' growth as the mechanism research is of great importance for their size control, large‐scale preparation, and for the exploration of applications in a wide range of fields. Finally, we will discuss the potential applications in several directions, including optical, electrical, mechanical, and biological fields, as well as our perspectives to future developments. Abstract : We present a review of fullerene (C60 ) nanowires in which we will first describe the recent development in the material preparations, analytical techniques, crystal structures, chemical compositions, and the investigations of polymerization processes. Afterward, we will discuss the mechanistic studies on the nanowires' growth, followed by discussion of the potential applications in several directions, including optical, electrical, mechanical, and biological fields, as well as our perspectives to the future development.